1702 N.H. Laws ch. 7: An Act for the Punishment of Criminall Offenders, in 1 Laws of New Hampshire: Province Period 679 (1904) - (:unkn) unknown (My University, 1702)
Prohibited riding or going armed offensively to cause fear or affray of the people.
Keywords: GOING ARMED